11.9k views
12 votes
-2(x-3)+4x = -(-x+1) SOLVE EQUATION AND SHOW STEPS ...NEED ANSWER NOW

User Pabigot
by
5.7k points

1 Answer

9 votes

Answer:

x=-7

Explanation:

-2(x−3)+4x=−(−x+1)

Step 1: Simplify both sides of the equation.

−2(x−3)+4x=−(−x+1)

−2)(x)+(−2)(−3)+4x=x+−1(Distribute)

−2x+6+4x=x+−1

(−2x+4x)+(6)=x−1(Combine Like Terms)

2x+6=x−1

2x+6=x−1

Step 2: Subtract x from both sides.

2x+6−x=x−1−x

x+6=−1

Step 3: Subtract 6 from both sides.

x+6−6=−1−6

x=-7

User Damgaard
by
6.1k points